(untitled) (International journal of medical sciences, 2025)
Electric-hybrid vehicles (EHV) combine internal combustion and electric propulsion to balance performance, efficiency, and sustainability. This paper examines the technological evolution, challenges, and future prospects of EHVs within the global automotive industry.